Solketal Production by Glycerol Acetalization Using Amberlyst-15 Catalyst - Hary Sulistyo; Edwin Nur Huda; Tri Sarifah Utami; Wahyudi B Sediawan; Suprihastuti Sri Rahayu; Muhammad Mufti Azis (ASEAN Journal of Chemical Engineering, 2020)
Glycerol, as a by-product of biodiesel production, has recently increased due to the rapid growth of the biodiesel industry. Glycerol utilization is needed to increase the added value of glycerol. Glycerol can be converted to solketal, which can be used as a green fuel additive to enhance an octane or cetane number. Conversion of glycerol to solketal was conducted via acetalization reaction with acetone using amberlyst-15 as the catalyst. The objective of present study was to investigate the effect of some operation conditions on glycerol conversion. Furthermore, it also aimed to develop a kinetic model of solketal synthesis with amberlyst-15 resins. The experiment was conducted in a batch reactor, equipped with cooling water, thermometer, stirrer, and a water bath. The variables that have been investigated in the present work were reaction temperature, reactants molar ratio, catalyst loading, and stirrer speed for 3 hours of reaction time. Temperatures, reactants molar ratio, and stirrer speed appeared to have a significant impact on glycerol conversion, where the higher values led to higher conversion. On the other hand, in the presence of catalyst, the increase of catalyst loading has a less significant impact on glycerol conversion. The results showed that the highest glycerol conversion was 68.75%, which was obtained at 333 K, the reactant’s molar ratio was  4, the amount of catalyst was 1 wt%, and stirrer speed of 500 rpm. Based on the pseudo-homogeneous kinetic model, the resulting kinetic model suitable for this glycerol capitalization. The value of parameters k and Ea were 1.6135 108 min-1 and 62.226 kJ mol-1,respectively. The simulation model generally fits the experimental data reasonably well in the temperature range of 313-333 K.